The Dynamics of Suspended Sediment in a Typical Alpine Alluvial River Reach: Insight From a Seasonal Survey. Issue 12 (18th December 2019) - Misset, C.; Recking, A.; Legout, C.; Valsangkar, N.; Bodereau, N.; Zanker, S.; Poirel, A.; Borgniet, L.
Abstract: The transport of suspended sediment is associated with important social, economic, and environmental issues. It is still unclear, however, how suspended sediments eroded on hillslopes are transferred downstream through the river system. In this study, we aimed to investigate this process by applying a sediment budget approach to a typical 3.5‐km‐long Alpine braided reach. Using high‐frequency suspended load measurements combined with Monte Carlo simulations for uncertainty propagation, we observed a significant buffering behavior of the reach studied. Thirty‐two of the 48 events observed during the 2‐month campaign showed significant differences between upstream and downstream mass transported as suspension, despite the reach studied was short compared to the upstream drainage area (130 km 2 ). These differences at the event scale varied widely within an envelope comprised between a net erosion equivalent to 74% of upstream suspended mass and a net deposition equivalent to 71%. Budgets were found to be controlled at a nearly instantaneous time scale by the liquid discharges and the suspended sediment concentrations in an opposite way: for low upstream concentrations, net erosion increased when the discharges increased, while above a certain concentration, net deposition increased when the concentrations increased. Moreover, coarse particles mobility in the reach (characterized via bedload transport measurements) appeared to have a strong influence on the availability of suspended particles as both quantities evolved concomitantly through time. These observations have important implications for our understanding and modeling of the transfer of suspended particles in gravel bedded streams. Key Points: Alluvial gravel bedded streams can act as sediment buffers on suspended load Net erosion and deposition of suspended sediment are controlled by both the water discharge and the suspended sediment concentration The mobility of coarse particles exerts a significant control on suspended sediment availability